Endoscopic cholecystoenteric stent migration as a cause of gallstone ileus - Maestro de Castro, José Luis; Veleda Belanche, Sandra; Estébanez Peláez, Guillemo; Acebes García, Fernando; Pacheco Sánchez, David (Cirugía del Uruguay, 2025)
A 91-year-old woman with a history of recurrent biliary colic and chronic cholecystitis, previously treated by endoscopic endoluminal drainage with placement of an AXIOS 15-10 cholecystoduodenal prosthesis, with a good evolution after the procedure.